2011
DOI: 10.2337/dc11-0099
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Management of Diabetes and Metabolic Risk Factors in Thai Adults

Abstract: OBJECTIVETo determine the prevalence of impaired fasting glucose (IFG) and undiagnosed and diagnosed diabetes in Thai adults in 2009 and examine the extent of changes in proportions of diagnosis, treatment, and control for blood glucose, high blood pressure, and high total cholesterol between 2004 and 2009.RESEARCH DESIGN AND METHODSData from the multistage cross-sectional National Health Examination Survey (NHES) IV of 18,629 Thai adults aged ≥20 years conducted in 2009 were used to analyze and compare with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
135
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(143 citation statements)
references
References 12 publications
5
135
2
1
Order By: Relevance
“…Figure 1 shows the map of the WPR, and Table 2 reports the temporal changes in the prevalence of diabetes in these countries. The rising trend in the developing countries is considerably steeper compared with the developed countries (1,12,14,15,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). In recent decades, apart from the WHO STEPS studies (11), there have been very few national diabetes studies for the Pacific Ocean nations (14).…”
Section: The Diabetes Epidemic In the Pacific Region And In Asia Wprmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows the map of the WPR, and Table 2 reports the temporal changes in the prevalence of diabetes in these countries. The rising trend in the developing countries is considerably steeper compared with the developed countries (1,12,14,15,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). In recent decades, apart from the WHO STEPS studies (11), there have been very few national diabetes studies for the Pacific Ocean nations (14).…”
Section: The Diabetes Epidemic In the Pacific Region And In Asia Wprmentioning
confidence: 99%
“…In Thailand, the National Health Examination Survey showed that the diabetes prevalence in people aged $15 increased from 2.5% in 1991 to 4.6% in 1997 and to 6.8% in 2004 (32). In 2009, their National Health Examination Survey (33) found the prevalence of impaired fasting glucose was 10.6% and diabetes was 7.5% (of which 35.4% were undiagnosed cases) in adults aged $20 years. These prevalences were likely to be underestimates because diagnosis relied only on a single FPG, history of physician diagnosis, and information on medications (33).…”
Section: The Diabetes Epidemic In the Pacific Region And In Asia Wprmentioning
confidence: 99%
See 1 more Smart Citation
“…Food types associated with these changes in the nutritive value of Thai diets are connected to rising incomes and an increasing desire for dietary convenience. So consumption of instant foods (particularly instant noodles), snack foods (such as potato chips), soft drinks and sweet cakes and bread products are all rising (Aekplakorn, 2011). When examined overall it has recently been shown that sugar sweetened beverages lead the way in Thailand for transitional caloric excess (Baker and Friel, 2014).…”
mentioning
confidence: 99%
“…Thailand's rapid socio-economic development in the last 4 decades leads to urbanization (Lim, Kjellstrom, et al, 2009), and sedentary work. People consume more calories and more fat, sugar and salt (Aekplakorn et al, 2011;Lim et al, 2014;Pitayatienanan et al, 2014). Urbanization altered lifestyle with more alcohol consumption and a higher incidence of non-communicable diseases such as hypertension, high cholesterol and obesity (Wakabayashi et al, 2015).…”
mentioning
confidence: 99%